Ethno-STEAM based ReMIS (read, make video, identify, solve problem) learning model to improve critical thinking abilities and digital literacy - Irmawati, Irmawati; Mauliana, Ana; Hutapea, Bilferi (Jurnal Gantang, 2025)
This study aims to describe the effect of the Ethno-STEAM-based ReMIS learning model on students' critical thinking and digital literacy skills. The primary issue of this study is the low level of critical thinking and digital literacy skills in the technological era, which hinders students from analyzing information and adapting to digital-based learning. The method used in this study is a quantitative, quasi-experimental design that directly tests the effect of the Ethno-STEAM-based ReMIS learning model on students' critical thinking and digital literacy skills, employing a pretest and posttest non-equivalent control group design. The research sample employed a purposive sampling method, comprising 26 students from class 2024A and 24 students from class 2024B. The results showed that the application of the Ethno-STEAM-based ReMIS learning model was significantly effective in improving students' critical thinking skills, with an average increase of 79.85 students and an N-Gain of 0.459. The Ethno-STEAM-based ReMIS learning model significantly improved students' digital literacy with an average increase of 77.46 and an N-Gain of 0.418. The implementation of the Ethno-STEAM-based ReMIS learning model represents a significant learning innovation in higher education, capable of enhancing the quality of students' science learning outcomes through a culturally informed approach.